2021
DOI: 10.1002/1873-3468.14229
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 nucleocapsid protein interacts with immunoregulators and stress granules and phase separates to form liquid droplets

Abstract: The current work investigated SARS-CoV-2 Nucleocapsid (NCAP or N protein) interactors in A549 human lung cancer cells using a SILAC-based mass spectrometry approach. NCAP interactors included proteins of the stress granule (SG) machinery and immunoregulators. NCAP showed specific interaction with the SG proteins G3BP1, G3BP2, YTHDF3, USP10 and PKR, and translocated to SGs following oxidative stress and heat shock. Treatment of recombinant NCAP with RNA isolated from A549 cells exposed to oxidative stress-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 125 publications
0
17
0
1
Order By: Relevance
“…The SARS-CoV-2 E protein viroporin increases NLRP3 inflammasome activation in both murine and human macrophages in a biphasic manner [ 503 ] by first suppressing NLRP3 inflammasome activation to aid viral replication leading to advanced disease states that promote the activation of NLRP3 inflammasomes [ 503 ]. The activation of NLRP3 inflammasome is often associated with the development of severe COVID-19 [ 504 , 505 , 506 ] and increased oxidative stress [ 507 ], while the production of inflammatory cytokines, including IL-β, may fuel the development of cytokine storms and excess oxidative stress to complete a positive feedback cycle [ 508 , 509 , 510 , 511 , 512 ] that enhances N protein LLPS [ 513 ]. This unique biphasic effect may be a reflection of how the SARS-CoV-2 virus interacts with DDX3X and SGs during viral replication ( Figure 1 ).…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The SARS-CoV-2 E protein viroporin increases NLRP3 inflammasome activation in both murine and human macrophages in a biphasic manner [ 503 ] by first suppressing NLRP3 inflammasome activation to aid viral replication leading to advanced disease states that promote the activation of NLRP3 inflammasomes [ 503 ]. The activation of NLRP3 inflammasome is often associated with the development of severe COVID-19 [ 504 , 505 , 506 ] and increased oxidative stress [ 507 ], while the production of inflammatory cytokines, including IL-β, may fuel the development of cytokine storms and excess oxidative stress to complete a positive feedback cycle [ 508 , 509 , 510 , 511 , 512 ] that enhances N protein LLPS [ 513 ]. This unique biphasic effect may be a reflection of how the SARS-CoV-2 virus interacts with DDX3X and SGs during viral replication ( Figure 1 ).…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
“…Oxidative stress induces the formation of SGs [ 87 ], and N protein LLPS induced by oxidative stress in vitro facilitates its partitioning into SGs to sequester G3BP1 [ 228 , 513 ]. Similar to other condensates formed via LLPS, N protein condensates can be tuned by the concentration of RNA where increasing RNA gradient with a fixed protein concentration at 10 μΜ caused N protein to increase viscosity from droplets to gel-like, and, eventually, solid assemblies [ 270 , 547 ], whereas phosphorylation of the serine/arginine (S/R)-rich region in the central IDR of the N protein can tune the viscosity and modulate N protein condensate assembly [ 278 ].…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, N protein inhibits the host stress response through SGs attenuation by sequestering G3BP1/2 through its interaction with these proteins and direct interaction with host mRNAs [51]. N protein can also specifically interact with G3BP1/2, leading to a reduction in the size and/or number of stress granules [52][53][54][55][56][57]. A short sequence (residues 15-18) in the IDR NTD or three arginine residues (R92, R107, and R149) in the NTD may also play an important role in its interaction with G3BP1 and modulation of stress granules.…”
Section: Nucleocapsid Protein Undergoes Liquid-liquid Phase Separatio...mentioning
confidence: 99%
“…The differential distribution of the two motifs underscores the potentially different roles of the UTRs and the central region in viral genome packaging. Studies have suggested that phase separation is involved in the selecting the single RNA genome and ensuring its compactness [14][15][16] . In such a model, the binding of N proteins to the 5′-and 3′-UTRs promotes liquid-liquid phase separation (LLPS), whereas the association of N proteins with the central region enhances the fluidity and solubilization of the viral genome and limits its entanglement with other large RNA molecules, thereby increasing the packaging efficiency 17,18 .…”
Section: Main Textmentioning
confidence: 99%